Design, Synthesis and Biological Evaluation of Novel Inhibitors of Trypanosoma brucei Pteridine Reductase 1 - Spinks, Daniel (WILEY-VCH Verlag, 2011)
Genetic studies indicate that the enzyme pteridine reductase 1 (PTR1) is essential for the survival of the protozoan parasite Trypanosoma brucei. Herein, we describe the development and optimisation of a novel series of PTR1 inhibitors, based on benzo[d]imidazol-2-amine derivatives. Data are reported on 33 compounds. This series was initially discovered by a virtual screening campaign (J. Med. Chem., 2009, 52, 4454). The inhibitors adopted an alternative binding mode to those of the natural ligands, biopterin and dihydrobiopterin, and classical inhibitors, such as methotrexate. Using both rational medicinal chemistry and structure-based approaches, we were able to derive compounds with potent activity against T. brucei PTR1 ([Image: see text]=7 nm), which had high selectivity over both human and T. brucei dihydrofolate reductase. Unfortunately, these compounds displayed weak activity against the parasites. Kinetic studies and analysis indicate that the main reason for the lack of cell potency is due to the compounds having insufficient potency against the enzyme, which can be seen from the low K(m) to K(i) ratio (K(m)=25 nm and K(i)=2.3 nm, respectively).